E-Service Quality Dynamics and Global Customer Loyalty Impact: Dinamika Kualitas Layanan Elektronik dan Dampak Loyalitas Pelanggan Global - Rahmayanti , Siti Rahardhini Dwi; Oetarjo, Mas (Indonesian Journal of Law and Economics Review, 2024)
This study examines how e-service quality, e-satisfaction, and e-trust affect e-customer loyalty among Shopee users in Sidoarjo. Using a quantitative approach with a sample of 96 participants, data analysis via partial least squares (PLS) reveals significant impacts on e-customer loyalty. Implications suggest Shopee should enhance responsiveness and accuracy for improved customer loyalty. Limitations include a small sample size and focus on specific variables, prompting future research to explore additional factors such as online shopping experience. Highlight: E-commerce loyalty dynamics. Quantitative analysis method. Enhancing Shopee's competitiveness. Keyword: e-service quality, e-satisfaction, e-trust, e-customer loyalty, Shopee